Penerapan Model Problem Based Instruction (PBI) dengan Media Kartu Pintar untuk Meningkatkan Kualitas Pembelajaran IPA pada Peserta Didik Kelas IV SDN 211/IX Mendalo Darat - Rosinah Rosinah (Jurnal Ilmiah Dikdaya, 2020)
The background of the problem in science learning, teachers do not involve students in investigations, students are less trained in developing work (products). The concepts that are mastered by students are only given rote by the teacher, students are not taught through a problem-oriented discovery process in everyday life. Based on this problem, the most appropriate solution is to implement a smart card media with a PBI model. In particular, it is improving teacher skills, student activities, and learning outcomes in science learning for class IV SDN 211 / IX Mendalo Darat. This research is a classroom action research, and uses a Problem Based Instruction model with smart card media in three cycles. Consists of two meetings and four stages in each, namely planning, implementing, observing, and reflecting. The results showed: (1) the skills of the teacher in obtaining an average score of the two meetings in cycle 1 were 21.5 with sufficient criteria; cycle 2 obtained a score of 27 with good criteria. The score obtained in cycle 3 is 30.5 and is included in the good category. (2) The activity of students obtaining an average score from the two meetings in cycle 1 was 21.85 with sufficient criteria; In cycle 2, a score of 24.35 was obtained with good criteria. For cycle 3, obtained a score of 31.2 good categories. (3) The learning outcomes of students obtaining an average percentage of classical completeness from the two meetings in cycle 1 was 55.41%. Obtained the percentage of classical completeness in cycle 2 is 68%. The percentage of classical completeness in cycle 3 was 81%. The indicators of success that have been achieved in the results of this study indicate that this research is declared successful. Through the Problem Based Instruction (PBI) model with smart card media, the conclusions of this study can improve teacher skills, student activities and learning outcomes of grade IV SDN211 / IX Mendalo Land. It is recommended for teachers that before starting learning with the Problem Based Instruction model with smart card media the teacher needs careful preparation